The non-planarity of the Benzene Molecule in the X-ray Structure of the Chelated Bismuth(III) Heteroboroxine Complex Is not Supported by Quantum Mechanical Calculations - Fanfrlík, Jindřich; Sedlák, Robert; Pecina, Adam; Rulíšek, Lubomír; Dostál, Libor; Moncóľ, Ján; Růžička, Aleš; Hobza, Pavel (Royal Society of Chemistry, 2015)
The non-planarity of the benzene moiety in the crystal of a chelated bismuth(III) heteroboroxine complex was not supported by DFT-D quantum chemical calculations. The observed bent structure of benzene is in fact a superimposition (thermal average) of the ensemble of thermally populated benzene structures in the complex studied.